Odpowiedzi

2009-09-20T10:55:03+02:00
1.)(tg²α-sin²α)ctg²α=sin²α

(tg²α-sin²α)ctg²α=sin²α
L=1²-cos²α=sin²α==>L=P

2.)cos⁴α+sin⁴α=1-2sin²α x cos²α

cos⁴α+sin⁴α=1-2sin²α x cos²α
cos⁴α+2sin²α x cos²α+sin⁴α=1
(cos²α+sin²α)²=1
1=1
  • Użytkownik Zadane
2009-09-20T10:59:17+02:00

cos⁴α+sin⁴α=1-2sin²α x cos²α
cos⁴α+2sin²α x cos²α+sin⁴α=1
(cos²α+sin²α)²=1
1=1





2009-09-20T11:03:04+02:00
Aby rozwiązać te zadania trzeba wiedzieć, że:
sin²α + cos²α = 1
sin α/cos α = tg α
tg α = 1/ctg α

i umieć odpowiednio je przekształcić.


(tg²α-sin²α)ctg²α=sin²α
tg²α × ctg²α - sin²α × ctg²α = sin²α
1 - sin²α × cos²α/sin²α = sin²α
1 - cos²α = sin²α
sin²α = sin²α


cos⁴α+sin⁴α=1-2sin²α x cos²α
cos⁴α + sin⁴α = sin²α + cos²α - 2sin²α x cos²α
cos⁴α + sin⁴α - sin²α - cos²α = - 2sin²α x cos²α
cos²α × (cos²α - 1) + sin²α × (sin²α - 1) = - 2sin²α x cos²α
cos²α × (-sin²α) + sin²α × (-cos²α) = - 2sin²α x cos²α
- 2sin²α x cos²α = - 2sin²α x cos²α